Bacillus subtilis RecA, DisA, and RadA/Sms Interplay Prevents Replication Stress by Regulating Fork Remodeling - Torres, Rubén; Alonso, Juan C. (Frontiers in Microbiology, 2021)
Reviving Bacillus subtilis spores require the recombinase RecA, the DNA damage checkpoint sensor DisA, and the DNA helicase RadA/Sms to prevent a DNA replication stress. When a replication fork stalls at template lesions, RecA filaments onto the lesion-containing gap and the fork is remodeled (fork reversal). RecA bound to single-strand DNA (ssDNA) interacts with and recruits DisA and RadA/Sms on the branched DNA intermediates (stalled or reversed forks), but they limit RecA activities and DisA suppresses its c-di-AMP synthesis. We show that RecA, acting as an accessory protein, activates RadA/Sms to unwind the nascent lagging-strand of the branched intermediates rather than to branch migrate them. DisA limits the ssDNA-dependent ATPase activity of RadA/Sms C13A, and inhibits the helicase activity of RadA/Sms by a protein-protein interaction. Finally, RadA/Sms inhibits DisA-mediated c-di-AMP synthesis and indirectly inhibits cell proliferation, but RecA counters this negative effect. We propose that the interactions among DisA, RecA and RadA/Sms, which are mutually exclusive, contribute to generate the substrate for replication